Three-dimensional acoustic circuits with coupled resonators in phononic crystals. (13th October 2022) - Ma, Tian-Xue; Li, Xiao-Shuang; Tang, Xiao-Lei; Su, Xiao-Xing; Zhang, Chuanzeng; Wang, Yue-Sheng
Abstract: In this study, we propose the three-dimensional (3D) phononic crystal-based coupled resonator waveguides (PnCCRWs) for the guidance of acoustic waves along complex routes. The proposed 3D PnC exhibits a complete acoustic band-gap. The point defect mode with a frequency in the band-gap is achieved via the introduction of a point defect into the perfect PnC. The 3D PnCCRWs are constructed by appropriately setting the PnC point defects in the designed paths. These PnC point defects interact with the neighboring ones, which leads to the propagation of the acoustic wave energy along the designated PnCCRWs. Notably, the interaction between the neighboring PnC point defects can be well described by the tight-binding model. The waveguiding ability is demonstrated numerically and experimentally for three different PnCCRWs integrated in the same PnC structure. In addition, the viscothermal effect on the transmission properties of the PnCCRWs is also investigated. The proposed 3D PnCCRWs exhibit their flexibility, which may stimulate additional design rules for complex 3D phononic circuits. Highlights: The design of phononic crystal-based coupled resonator waveguides is proposed. The waveguiding along 3D complex routes is verified numerically and experimentally. The tight-binding model describes the interaction between phononic crystal defects. The viscothermal effect on the transmission property is investigated.